The significance of human spermatozoa vacuoles can be elucidated by a novel procedure of array comparative genomic hybridization. Issue 4 (6th February 2018) - Berkovitz, Arie; Dekel, Yaron; Goldstein, Revital; Bsoul, Shhadeh; Machluf, Yossy; Bercovich, Dani
Abstract: STUDY QUESTION: Is there an association between spermatozoon genomic stability and vacuolar morphology and location? SUMMARY ANSWER: The genomic stability of spermatozoa is associated with specific characteristics of vacuolar morphology (depth) and location (cellular compartment, i.e. nucleus and equatorial region). WHAT IS KNOWN ALREADY: Genetic anomalies in sperm are correlated with semen abnormalities, yet the advantage of morphologically based selection of spermatozoa for IVF according to current criteria is controversial. Selection criteria based on the number of vacuoles and their size have been proposed and are widely applied. Nevertheless, it has not improved the ICSI success rates, suggesting the currently used vacuole criteria are incomplete. STUDY DESIGN, SIZE, DURATION: Normal sperm according to Motile Sperm Organelle Morphology Examination criteria (MSOME) and common vacuole grading were evaluated. An additional evaluation of sperm vacuole morphology according to novel vacuole criteria (i.e. location and depth) was conducted. An assessment to align these specific vacuolar morphology features with genomic stability was conducted among spermatozoa from infertile patients and healthy fertile donors aged 24–38 between June 2015 and July 2016. PARTICIPANTS/MATERIALS, SETTING, METHODS: Single spermatozoa ( n = 53) from 16 infertile patients and 14 fertile donors were morphologically and genetically evaluated. Each spermatozoon was examined morphologically, by ultra-magnification ×6300, and genetically by a novel comparative genomic hybridization protocol, without the use of reference DNA, to assess chromosomal instability as evident by copy number variations (CNV). MAIN RESULTS AND THE ROLE OF CHANCE: We established an association between genomic stability and vacuolar morphology as a base for a new classification according to novel vacuolar criteria, specifically depth and location. Genomic instability was found to be related to these two main features of vacuoles and, surprisingly not to the number and size of vacuoles as in the previously proposed classifications. High CNV spermatozoa were characterized by vacuoles located in the nucleus and/or equatorial segment or by deep vacuoles, while, low CNV spermatozoa were characterized by a complete lack of vacuoles or non-deep vacuoles not located in the nucleus/equatorial segment. A putative threshold of 265 CNV was deduced to distinguish between genetically stable and unstable spermatozoa, and 94% of the tested spermatozoa segregated accordingly. LIMITATIONS REASONS FOR CAUTION: A relatively small sample of spermatozoa were examined—53 in total. However, the association between vacuoles location and morphology and genomic stability was significant. This is the first study evaluating spermatozoon genomic stability with respect to vacuole morphology according to novel vacuole criteria (i.e. location and depth) and further investigation is warranted to verify the value of these criteria in larger sample size clinical studies. WIDER IMPLICATIONS OF THE FINDINGS: Our results, which are based on spermatozoon vacuoles morphological classification and genomic parameters, indicate an association between vacuoles morphology and location and genomic stability. The data presented herein suggest the existence of subpopulations of spermatozoa potentially appropriate for IVF–ICSI, as they appear normal according to the current MSOME and vacuoles classification, however they are almost certainly genetically damaged. As current criteria have yet to achieve an unequivocal evaluation of the implantation potential of a given spermatozoon, we propose novel criteria, based on specific vacuolar morphological traits; depth and location, as these were found aligned with genomic findings. STUDY FUNDING/COMPETING INTEREST(S): No funding was received for this study. The authors have no conflict of interest to declare. TRIAL REGISTRATION NUMBER: N/A.